2020
DOI: 10.1021/acsami.0c00302
|View full text |Cite
|
Sign up to set email alerts
|

pH and Glutathione Synergistically Triggered Release and Self-Assembly of Au Nanospheres for Tumor Theranostics

Abstract: Theranostic agents based on near-infrared absorption which integrate both imaging and therapeutic functions have attracted considerable attention. However, because of the interference signal, indiscriminate treatment usually causes side effects on normal tissues during tumor treatment. To address this limitation, we propose a new synergistically triggered mechanism, release and self-assembly of Au nanospheres, for tumor theranostics based on the synergistic effect of H+ and glutathione on the tumor microenviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 52 publications
(91 reference statements)
0
35
0
Order By: Relevance
“…As a proof of concept study, the penetration depth of a 405 nm laser remains limited, but the current strategy for manipulating Au particles in vivo can be extended to other types of light-triggered assembly nanoparticles, which can be triggered by lights with wavelengths that are more suitable for clinical applications. Qiwei Tian and Shiping Yang et al [ 68 ] proposed a novel synergistic triggering mechanism to realize the self-assembly of gold nanospheres. Au@ZIF-8 does not produce photoacoustic signal and photothermal conversion capability in normal tissue.…”
Section: Self-regulating Photothermal Conversion Systemmentioning
confidence: 99%
“…As a proof of concept study, the penetration depth of a 405 nm laser remains limited, but the current strategy for manipulating Au particles in vivo can be extended to other types of light-triggered assembly nanoparticles, which can be triggered by lights with wavelengths that are more suitable for clinical applications. Qiwei Tian and Shiping Yang et al [ 68 ] proposed a novel synergistic triggering mechanism to realize the self-assembly of gold nanospheres. Au@ZIF-8 does not produce photoacoustic signal and photothermal conversion capability in normal tissue.…”
Section: Self-regulating Photothermal Conversion Systemmentioning
confidence: 99%
“…Non-covalent interactions, such as electrostatic interactions, hydrogen bonding, and hydrophobic-hydrophobic interactions are driving forces to induce self-assembly of amphiphilic block copolymers. The stability of the self-assembly can be influenced by several environmental factors, including the pH, temperature, polymer concentration, and ionic strength [ 22 , 23 , 24 , 25 ]. Bishara et al synthesized stereocomplex particles composed of an enantiomeric triblock copolymer (PLA-PEG 2000 -PLA) by blending in acetonitrile solutions [ 26 ].…”
Section: Drug Deliverymentioning
confidence: 99%
“…ZIF-8, which is a metalorganic framework formed by zinc (Zn 2+ ) and imidazole, [11,12] is a widely used smart nano-delivery agent, as it can be rapidly degraded by weakly acidic and highly expressed glutathione (GSH) in tumors. [13][14][15] For example, An et al [16] reported an engineered smart agent based on ZIF-8-coated gold nanospheres. In normal tissues, the ZIF-8 coating is very stable and prevents the aggregation of the gold nanospheres; however, the nanospheres are released in the tumor owing to destruction of ZIF-8.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 , 14 , 15 ] For example, An et al. [ 16 ] reported an engineered smart agent based on ZIF‐8‐coated gold nanospheres. In normal tissues, the ZIF‐8 coating is very stable and prevents the aggregation of the gold nanospheres; however, the nanospheres are released in the tumor owing to destruction of ZIF‐8.…”
Section: Introductionmentioning
confidence: 99%